Three futures for postcrisis banking in the Americas: The financial trilemma and the Wall Street complex - Gary A. Dymski (Levy Economics Institute of Bard College, 2010)
This would seem an opportune moment to reshape banking systems in the Americas. But any effort to rethink and improve banking must acknowledge three major barriers. The first is a crisis of vision: there has been too little consideration of what kind of banking system would work best for national economies in the Americas. The other two constraints are structural. Banking systems in Mexico and the rest of Latin America face a financial regulation trilemma, the logic and implications of which are similar to those of smaller nations' macroeconomic policy trilemma. The ability of these nations to impose rules that would pull banking systems in the direction of being more socially productive and economically functional is constrained both by regional economic compacts (in the case of Mexico, NAFTA) and by having a large share of the domestic banking market operated by multinational banks. For the United States, the structural problem involves the huge divide between Wall Street megabanks and the remainder of the U.S. banking system. The ambitions, modes of operation, and economic effects of these two different elements of U.S. banking are quite different. The success, if not survival, of one element depends on the creation of a regulatory atmosphere and set of enabling federal government subsidies or supports that is inconsistent with the success, or survival, of the other element.
Keywords: E5; F3; G1; G2; O1; P5; 330; banking; financial crisis; trilemma; Wall Street; Mexico; United States; financial regulation; megabanks; regional compacts; NAFTA